THE USE OF FORMATIVE EVALUATION IN THE DEVELOPMENT OF SPATIAL BUILDINGS FOR ELEMENTARY SCHOOL STUDENTS BASED ON AUGMENTED REALITY - Sapta, Andy; Nisa, Uliya Khoirun (Al-Bidayah : Jurnal Pendidikan Dasar Islam, 2024)
Learning media for elementary school students is an important tool that has developed in line with technological advances. Therefore, this study aims to evaluate learning media development on building space materials using Augmented Reality (AR) technology. Formative evaluation consists of initial analysis and stages. In addition, this study used 15 SDIT students, Alam Nurul Islam and Yogyakarta. The questionnaires distributed were related to the respondents' attitudes and responses. The results showed that students reacted positively to the development of AR learning media, and validation from experts obtained a feasibility percentage of 85.34% with valid criteria. Meanwhile, student responses expressed a sense of pleasure when the teacher explained the use of AR learning media. Mathematics material is easy to understand because geometry objects are realized as 3D objects through AR learning media. In addition, students are more active in learning by using AR learning media.